EDITORIAL: (IN)SUFFICIENT LEGAL BASIS FOR THE PROPOSAL FOR REFORM OF REGULATION 883/2004 PRESENTED BY THE EUROPEAN COMMISSION ON 13.12.2016 - Sánchez-Rodas Navarro, Cristina (e-Revista Internacional de la Protección Social, 2017)
Editorial